Pengaruh Penerapan Akuntansi Lingkungan, Biaya Lingkungan, dan Tata Kelola Perusahaan terhadap Biaya Modal - Ramadhan, Muhammad Andika; Dewi, R Rosiyana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of environmental accounting, environmental costs and corporate governance on capital costs. The independent variables used in this research are Environmental Accounting, Environmental Costs, and Corporate Governance. Meanwhile, the Dependent Variable in this research is Capital Cost. The analytical method used in this research is multiple linear regression analysis with purposive sampling technique. In this research, the author used secondary data taken from annual reports and sustainability reports of non-banking sector companies listed on the Indonesia Stock Exchange for 2019-2022. From the results of the research that has been carried out, it is concluded that environmental accounting variables, environmental costs and corporate governance have a negative effect on the cost of capital.